Algorithm for Internal State Financial Control by the Treasury of Russia: Problems and Solutions - N. N. Simko (Финансы: теория и практика, 2020)
The paper discusses an integrated research of implementing internal state financial control by the Federal Treasury. The aim of the study is to show the organization and stages (algorithm) of implementing internal state financial control, to identify problems and possible solutions. The relevance of the study determines the modern development of financial control, aimed at automation and digitalization. Scientific novelty is in systematizing problems of financial control and finding new solutions. The author uses methods of analysis, synthesis, induction, deduction, scientific abstraction, logical thinking, the dialectical method of cognition and observation. The study results in describing an algorithm for internal state financial control by the Treasury of Russia, and identifies problems (weaknesses) related to the planning and implementation of control measures in the financial and budgetary sphere, as well as possible solutions. The author points out the need to revise the procedures for implementing internal state financial control and its new forms with the current methods of financial control. The study suggests such a new form of financial control as automated remote financial monitoring, which warns on the impermissibility of violations in the financial and budgetary sphere. The author concludes that in order to automate and digitalize internal state financial control, it is necessary to create a unified information base, including systematized information according to the criteria set by the state. This will allow for a deeper economic analysis of using budgetary funds allocated by the state for certain purposes, at the stages of preliminary and subsequent control, that will improve and increase the efficiency of financial control, and save time and labor during control activities. The author recommends to improve the regulatory framework governing the implementation of financial control by the Russian Treasury, including internal state financial control.